Haematology of the Malaysian Swamp Buffalo (Bubalus bubalis) - Sulong, Adnan; Jainudeen, M.R.; Mohamad, Hilmi (1980)
R aematological values and total plasma protein concentration were determined from Jugular vein blood samples obtained from clinically healthy 2 to 4 year old swamp buffaloes of both sexes. The mean values for total RBC count, haemoglobin concentration and PCV were 8.8 X 106/ p.l, 13.4 g/dl and 39.2% respectively. The mean values for MCV, MCR and MCHC were 49.3 p.3, 16.5 pg and 34.1% respectively. The mean total WBC count was 10.7 X 103/p.l. The differential white cell counts for lymphocytes, neutrophils, monocytes, eosinophils and basophils were 54.2, 35.2, 3.7, 6.6 and 0.3 percent respectively. The mean total plasma protein value was 7.4 g/dl. Compared with the river buffalo and cattle, swamp buffaloes had higher total RBC count, haemoglobin concentration, PCV and total WBC count.